Phonon spectra of Cu₆PS₅Br superionic ferroelastic: experimental and theoretical studies - Studenyak, I.P.; Rushchanskii, K.Z.; Buchuk, R.Yu.; Stephanovich, V.O. (Condensed Matter Physics, 2007)
The anomalous temperature behavior of the Raman scattering bands at superionic phase transition of Cu₆PS₅Br is revealed. Using density functional perturbation theory within local density approximation, ab initio long-wavelength phonons have been obtained for high-symmetry cubic structure. In the calculated phonon spectrum two unstable modes indicate the experimentally observed sequence of ferroelastic and superionic phase transitions. Експериментально виявлено аномальну температурну поведiнку пiкiв раманiвського розсіювання свiтла при суперiонному фазовому переходi в Cu₆PS₅Br. Для високосиметричної кубiчної фази теоретично розраховано першопринципнi частоти довгохвильових фононiв з використанням теорії збурень функцiонала густини у локальному наближеннi. У фононному спектрi спостерiгаються дві нестабiльнi моди, якi вказують на експериментально спостережувану послiдовнiсть сегнетоеластичного i суперiонного фазових переходiв.